2020
DOI: 10.1074/jbc.ra120.014873
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 (COVID-19) structural and evolutionary dynamicome: Insights into functional evolution and human genomics

Abstract: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has challenged the speed at which laboratories discover the viral composition and study health outcomes. The small ~30-kb ssRNA genome of coronaviruses makes them adept at cross-species spread, but also enable a robust understanding of all the proteins the viral genome encodes. We have employed protein modeling, molecular dynamic simulations, evolutionary mapping, and 3D printing to gain a full proteome- and dynamicome-level un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…24 The recent development of the Viral Integrated Structural Evolution Dynamic Database (VIStEDD) should help further elucidate the viral proteome dynamics and their interaction with host cell receptors. 25 Respiratory viruses with monobasic cleavage sites typically have an expression profile confined to the aerodigestive tract. Viral replication is limited to these organs as the cleavage site is cleaved by few cellular proteases, restricting viral growth to these limited areas.…”
Section: Tmprss2 and Viral Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…24 The recent development of the Viral Integrated Structural Evolution Dynamic Database (VIStEDD) should help further elucidate the viral proteome dynamics and their interaction with host cell receptors. 25 Respiratory viruses with monobasic cleavage sites typically have an expression profile confined to the aerodigestive tract. Viral replication is limited to these organs as the cleavage site is cleaved by few cellular proteases, restricting viral growth to these limited areas.…”
Section: Tmprss2 and Viral Entrymentioning
confidence: 99%
“… 24 The recent development of the Viral Integrated Structural Evolution Dynamic Database (VIStEDD) should help further elucidate the viral proteome dynamics and their interaction with host cell receptors. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Also, these residues are the most conserved residues of N protein according to multiple sequence alignment results obtained from ESPript 3.0 (Robert & Gouet, 2014) ( Figure S3, supplementary material). According to a recent study, the amino acids, 331-333 were the most conserved yet dynamic site of N and involved in the multimerization of N protein (Gupta et al, 2020). The multimeric structure of N revealed that the conserved amino acids Val270, Phe274, Arg277, Asn285, Gly287, Phe286, and Asp288 are clustered and surface exposed, and thus could contribute to protein-protein interactions.…”
Section: Evaluating the Stability And Conformational Dynamics Of Ctd-mentioning
confidence: 99%
“…Structural level insights for coronavirus proteins are surprisingly deficient of human interaction partners. 10 A few of these proteins have been targeted for interaction assessments, such as the nucleocapsid protein 24 , 25 (shown below). It has been speculated that the understanding of virus–host interactions represents a major untapped potential of viral inhibitors.…”
Section: Sars-cov-2 Human Protein Interactionsmentioning
confidence: 99%